Response of Temperature-Related Rice Disaster to Different Warming Levels Under an RCP8.5 Emission Scenario in a Major Rice Production Region of China - Luo, Shuangyi; Jiang, Zhihong; Chou, Jieming; Tu, Gang; Wang, Shuyu (Frontiers in Climate, 2022)
Rice is the basic food for about 50% of the global population, and feeds two-thirds of the Chinese population. Under the influence of global change, extreme weather, and climate events increase in frequency, duration, and intensity, which affect food production substantially. In the medium-to-long term in the future, the impacts of climate change on food availability are likely to grow. In this work, we first define the rice damage indices and then use surface observation and regional climate downscaling results from the variable resolution model LMDZ4 driven by the six Coupled Model Intercomparison Project phase 5 (CMIP5) global climate models (GCMs) to describe the temporal-spatial characteristics and the future changes of the temperature-related rice damages in Northeast China and Central and East China, the major commercial rice production regions in China. Compared with the observation, LMDZ4 demonstrates its ability to reproduce the regional characteristics of both heat and chilling rice damages. Based on the future regional projections under the RCP8.5 pathway, future changes of rice damage under four temperature-rising categories of 1.5, 2, 3, and 4°C are estimated. In the two rice production regions, the future extent of heat-related damage for Northeast China is mostly limited to the western area, and the occurrence of heat damage generally increases with global warming levels, particularly when it is higher than 2°C. For Central and East China, the heat-related rice damage increases in both coverage and intensity. The region is also likely to have a faster increasing rate of heat damage than in Northeast China. When global warming reaches 3 and 4°C, the median heat-related damage spreads over almost the whole region of Central and East China. Moreover, the probability of regional-scale heavy level heat damage would be over 50% by the end of twenty-first century. On the other hand, the disastrous impact of a cold event affecting rice yield is reduced in both coverage and duration although the model projections over Northeast China show larger intermodel variability and uncertainty.